PENGARUH PEMBERIAN INSULIN-LIKE GROWTH FACTOR-I (IGF-I) DARI SERUM KUDA CROSSBREED BUNTING TERHADAP KETEBALAN ENDOMETRIUM MENCIT (Mus musculus) - Risna Y, Dyah Ayu Roro; Mulyati, Sri; Darsono, Roesno; Mustofa, Imam; Arimbi, Arimbi; Widjiati, Widjiati (Universitas Airlangga, 2018)
The purpose of the research was to know the effect of Insulin-Like Growth Factor-I (IGFI) derived from pregnant crossbreed mare serum (PMS) on endometrium thickness of mice (Mus musculus). The subject of this research were 35 female mice. The research was arranged by Completely Randomized Design (CRD) with seven treatment and five replications. The treatment were P0 = 10 ng/ml of physiological NaCl, P11 = 10 ng/ml of IGF-I PMS, P12 = 20 ng/ml of IGF-I PMS, P13 = 40 ng/ml of IGF-I PMS, P21 = 10 ng/ml of IGF-I recombinant mouse, P22 = 20 ng/ml of IGF-I recombinant mouse, and P23 = 40 ng/ml of IGF-I recombinant mouse. Observed variables include histopatological endometrium thickness of mice. The data were analyzed by Analysis of Variance (ANOVA), followed by HSD (Honestly Significant Difference) test. The data was also be analyzed using General Linear Model Univarieted to see the comparison between IGF-I PMS and recombinant mouse. The result showed that the addition of IGF-I PMS did not significantly affect (p>0,05) on endometrium thickness of mice . It showed that did not significantly difference (p>0,05) between the effect of IGF-I PMS and IGF-I recombinant mouse against the endometrium thickness of mice.